2020
DOI: 10.1111/zph.12797
|View full text |Cite
|
Sign up to set email alerts
|

History of indigenous Trypanosomacruzi infection in humans, animals and triatomines in California, USA

Abstract: This historical review highlights previously undescribed potential foci for sylvatic and domestic locally acquired Chagas disease in California. The review starts in the 1910s, when Trypanosoma cruzi was first discovered through scientific triatomine investigations. Next, the natural transition around the mid-1900s into clinical investigations of the domestic and peridomestic environments and their epidemiologic profiles is detailed. The review closes with the shift to applied genetic, diagnostic and scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Triatoma protracta has demonstrated that it will invade human dwellings in California and has led to serious allergic reactions, including anaphylaxis [19]. Our investigation has revealed the first documented report of T. cruzi in Mendocino County, California, and T. cruzi-infected triatomine invasion into a human dwelling in this region of California [20,21].…”
Section: Discussionmentioning
confidence: 67%
“…Triatoma protracta has demonstrated that it will invade human dwellings in California and has led to serious allergic reactions, including anaphylaxis [19]. Our investigation has revealed the first documented report of T. cruzi in Mendocino County, California, and T. cruzi-infected triatomine invasion into a human dwelling in this region of California [20,21].…”
Section: Discussionmentioning
confidence: 67%
“…20,35,36 California does have a long history of sylvatic enzootic transmission, and the reported frequency of camping and other nocturnal outdoor supports the potential for vector-borne infection in that state. 37 Additional overlapping risk factors among these positive donors were ever living in a rural area in a state with known vectorhuman transmission and having lived on property surrounded by open land (suggestive of potential exposure to sylvatic transmission cycles). Lastly, history of military service that included overnight field training was noted, which has previously been described as possible vectorborne transmission sources.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot exclude the possibility that these donors' infections were acquired in Texas, where the majority of US‐acquired cases have been identified 20,35,36 . California does have a long history of sylvatic enzootic transmission, and the reported frequency of camping and other nocturnal outdoor activity supports the potential for vector‐borne infection in that state 37 . Additional overlapping risk factors among these positive donors were ever living in a rural area in a state with known vector‐human transmission and having lived on property surrounded by open land (suggestive of potential exposure to sylvatic transmission cycles).…”
Section: Discussionmentioning
confidence: 99%
“…Chagas disease, caused by infection with the protozoan parasite Trypanosoma cruzi, continues to be the leading cause of non-ischemic cardiomyopathy and a public health concern in the Americas [1,2]. Most infected individuals acquire infection in childhood and experience subclinical chronic disease, in which 30% will insidiously progress to dilated cardiomyopathy and heart failure years to decades after initial infection [3].…”
Section: Introductionmentioning
confidence: 99%